Beyond communication - research as communicating: making user and audience studies matter - paper 2 - Brenda Dervin; CarrieLynn Reinhard; Fei C. Shen (Information Research: An International Electronic Journal)
Introduction. This is the written version of the keynote address (Making user studies matter: Thank you Mister Feynman and Monsieur Foucault) delivered by senior author Dervin. The paper is linked to the Invited Paper in this issue and like that paper, reports on a project involving a dialogue between researchers and practitioners in library and information science, human computer interaction, and communication focusing on gaps in our understandings of users and audiences as well as in our efforts to collaborate with each other to conduct and apply research to the design and implementation of information, library, communication, and media systems. Argument. Our main conclusion in Paper 1 was that the traditional modes used for communication in social science research are not doing the job for user and audience studies. We set out five propositions relating to this conclusion: (1) the traditional modes of communicating in the research enterprise are not working; (2) Do the social sciences matter? Some serious and fundamental attacks; (3) a call to focus on the special problematics of the social sciences: agency, structure, power and the good; (4) eschewing scientific recipes and scholarly creeds and bringing back the joys of adventuring and muddling; (5) the paradox of communicatingfreedom is another word for nothing left to lose. Conclusion. We argue for shared dialogue in communicating across the three fields studied here: this will introduce uncertainty, but, rather than relying upon 'authority', the individual will be encouraged through the exploration of that uncertainty, to make their own sense of the offerings of others.